SISTEM INFORMASI PEMASARAN BARANG DAN JASA PADA BATARA KOMPUTER BERBASIS WAP (Information Technology and Telematics, 2013)
God are Computer constitute a moving service  effort  deep  pemasan's  area  goods  and service. In give service to visitor or God's buyer candidate  Computer  provide  information  about price  and  goods  specification,  but  to  get  that  information visitor or buyer candidate shall come  directly  to  God  Computer  or  even  ask  that  information are telephonic. Get  bearing  thereto,  writer  makes  to  make the point that more effective to that service  user  candidate  without  has  to  visit  God Computer.  One  of  it  which  is  God  Computer provide  an  accessible  service  pass  cellular  telephone(  ponsel)  already  been proveded with  Wireles  Application  Protocol's  facility  (WAP) General PACket is service's Radio (GPRS). Kata kunci : Ponsel,WAP